UNSUR POSKOLONIAL DALAM NOVEL â€œMATAHARI TERBIT DI UTARAâ€ SUATU TINJAUAN SOSIOLOGI SASTRA - TALANGGAI, BREYVI YUSUF (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT In this research, theÂ  purposeÂ  is about to reach is.1) To verify the subtances postcolonialism on the novel â€œMatahari Terbit di Utara (sunrise up north) as resistant to colonialism. 2) To describe the different opinion between central and region. Research is a observation of literary sociology to postcolonialism and use descriptive method, that is describe or draw everything just the way it is. The data is taken or gathered, inventoryng and then being clasification and analysed. The resourche of this data consis of primary data. Meanwhile the secondary data that is from books of reference theory or literary knowledge and any other backup resourche. The result of this research explain as far the effect of legacy from colonialism within the civilized and resistance to colonialism in Indonesia especially on the novel â€œMatahari Terbit di Utaraâ€. Implication of the writer or mixed upÂ  the author of this novelÂ  has been formed of the fiction characters or the domination argument and idea on the novel is when the author placed opposition side of the region to central who more dominant. Â  keyword : literary sociology, subtance of postcolonialism, novel Matahari Terbit di Utara (sunrise up north).